Expression of Hedgehog Signaling Pathway Proteins in Basal Cell Carcinoma: Clinicopathologic Study - Deng LJ; Jia M; Luo SY; Li FZ; Fang S (Dove Medical Press, 2022)
Li-Jia Deng, Meng Jia, Si-Yu Luo, Feng-Zeng Li, Sheng Fang Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of ChinaCorrespondence: Sheng Fang, Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, No. 1, Youyi Road, Yuzhong District, Chongqing, 400016, People's Republic of China, Email fangshengderm@163.comObjective: Basal cell carcinoma (BCC) is the most common type of cancer with a growing incidence rate over recent decades. The increasing economic burden and incidence of BCC have generated major interest in developing targeted therapies for this disease. The critical role of the Hedgehog (Hh) pathway in the pathogenesis of BCC has become evidently demonstrated. The purpose of this study was to observe the expression of PTCH1 and Gli1 in BCC and further evaluate their relationship with clinicopathological features.Methods: This retrospective study included 84 patients with BCC. Information of 84 patients with pathologically diagnosed BCC (including location, sex, tumor size, pathological type, and depth of invasion) were collected, and tissue paraffin blocks were collected for immunohistochemical staining. Western blot analysis for PTCH1 and Gli1 were also performed. The staining intensity and percentage of stained cells were expressed as a histochemical score (HSCORE).Results: PTCH1 and Gli1 were overexpressed in BCC compared with adjacent normal epidermis. Our study found that the expression of PTCH1 and Gli1 in BCC in exposed sites was significantly higher than in non-exposed sites. Moreover, no significant difference was observed in sex, Breslow thickness, tumor size or pathological type (P> 0.05).Conclusion: PTCH1 and Gli1 were overexpressed in BCC. Higher PTCH1 and Gli1 expression were in exposed sites lesions. Our study suggests that UV radiation may be associated with aberrant activation of the Hh-PTCH1-Gli1 intercellular signaling pathway in BCC. The molecular mechanism of UV-related PTCH1 and Gli1 differential expression deserves more rigorous research in the future.Keywords: basal cell carcinoma, Hh pathway, UV radiation, PTCH1, Gli1